Research Trends Mathematics Concepts on Pre-Service Mathematics Teachers: A Bibliometric Analysis Using Vosviewer From 2017 To 2022 - Sugiarni, Rani; Herman, Tatang; Suryadi, Didi; Prabawanto, Sufyani; Inayah, Sarah (PRISMA, 2023)
Preparing qualified teacher candidates also helps to create a sustainable education system, therefore, the preparation of teacher candidates should be a priority for any education system that wants to achieve success and sustainability. Some research on prospective mathematics teachers has developed rapidly. This study aims to investigate: 1) what is the performance analysis of publication and citation-related metrics and their trends from pre-service teacher mathematics studies, and 2) what is the science mapping and network analysis of citation analysis, authorship partner analysis, and word partner analysis from pre-service teacher mathematics studies. A research method is a bibliometric approach using the Scopus database with two search keywords namely "pre-service teacher" and "mathematics concepts". A total of 181 documents related to the two keywords were distributed in the range of 2017-2022. Data analysis was done by performance analysis, science mapping, and network analysis using Publish or Perish and VOSviewer software. The results showed that publications related to the study of "pre-service teacher mathematics" with 337 citations from 118 documents. Research on "pre-service teacher" and "mathematics concepts" has grown rapidly in the last five years, Visualization Network co-authorship emergence is Suryadi from Indonesia. While the occurrence of keywords (co-occurrence) often appears among others teacher knowledge, concept map, professional development, stem education, and content mathematics. but there is still a gap for us to make new research as a development of previous research in the development of quality pre-service mathematics teachers.